The Narratives of Islamic School Students: Contesting Salafism in a Saudi-Wahabi Educational Institutions in Contemporary Jakarta - Jahroni, Jajang (Ulumuna, 2020)
This article deals with the reproduction of knowledge within the Saudi-Wahhabi educational institution named LIPIA in Jakarta. Contrary to many studies which tend to see this institution as a monolithic entity, this article argues its knowledge reproduction is diverse as a result of different actors and the social contexts involved in the process. Besides students with modernist and traditionalist backgrounds are present in the institution, the Tablighis and the Salafis are also involved, shaping the reproduction of knowledge are more complex than expected. Each group of students are trying to influence the circumnstances they live in resulting in the diversity of knowledge. Furthermore, despite the Saudi state imposes certain subjects and disciplines to be followed by students, students have their own ways of shaping their knowledge. While in-campus program is well-organized, out-campus life is hardly ever to control as students develop their own network and socialization. Students are exposed to different types of Indonesian larger social contexts.